A Performance Way Comparison of Docker Swarm and Kubernetes - ÜLKÜ, EYÜP EMRE (My University, 2022)
People always try to find the best way to deploy their applications. Thus, the first solution was bare metal servers. In the bare metal server solution, each server was responsible for one application but that required as many servers as the number of applications, and in addition that this solution also required so much space in the server room. Subsequently, virtualization technology emerges. This technology is based on the abstraction of computer hardware. Virtualization technology enables us to host multiple operating systems in one host. Virtualization brings along with many advantages. One of the significant benefits is to reduce the quantity of physical equipment needed in the data center and helps to scale our applications. One of the remarkable developments in information technologies is container technology which emerged in the middle of 2010. Containers allow to package an application with all the parts it needs, such as libraries and other dependencies, and deliver it as a single package. Docker, developed by Google, is the essential tool to use in container technologies. Docker resembles a virtual machine, but as opposed to a virtual machine, instead of creating a whole virtual operating system, Docker allows applications to use the same Linux kernel as the system they use. This provides a performance boost and reduces the size of the application. Also, the development of microservice-based applications in recent years has made container technologies widely used. Now, we can run each of our applications, perhaps thousands of containers. However, this solution brings with it another problem, how do we manage these containers? In recent years, there have been a few breaks in the server side, which underlies the rapidly developing information technologies. The last of these is container technology. Before virtualization, companies were running all their applications on physical servers, and these systems were getting complex over time, making even simple problems inextricable. Accordingly, in this study we compare Docker Swarm and Kubernetes in terms of their performances under heavy load, two of the most used tools for container management. Thus, we aim to inform readers about container management.
Keywords: virtualization; containers; docker; docker swarm; kubernetes.